2001
DOI: 10.1093/ps/80.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Source and Ratio of Xanthophyll Pigments on Broiler Chicken Pigmentation and Performance

Abstract: One experiment was conducted using 960 1-d-old, sexed broilers of Ross 308 strain from 1 to 43 d to evaluate if one type of chemically isomerized marigold with 25% of xanthophylls as zeaxanthin (SME-25) could produce pigmentation equivalent to the current addition of conventional marigold with 10% of xanthophylls as zeaxanthin (SME-10) plus canthaxanthin (CTX) in practical broiler diets (maize-wheat-soybean). Birds were allocated in 32 pens, in a randomized complete block design (four blocks x four treatments)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 15 publications
3
50
0
9
Order By: Relevance
“…Dietary xanthophyll level did not have any effect on growth performance, which is in agreement with previous research (Martínez et al 2004, Le Bihan-Duval et al 1998, Pérez-Vendrell et al 2001.…”
Section: Discussionsupporting
confidence: 92%
“…Dietary xanthophyll level did not have any effect on growth performance, which is in agreement with previous research (Martínez et al 2004, Le Bihan-Duval et al 1998, Pérez-Vendrell et al 2001.…”
Section: Discussionsupporting
confidence: 92%
“…Adv., 10 (11): 690-707, 2015 Pigments are highly susceptible to oxygen, light and temperature (Kerrer and Jucker, 1950). Deposition of carotenoids in skin, egg yolk or adipose tissue causes yellow coloration which makes it more acceptable and attractive by the consumers (Perez-Vendrell et al, 2001;Leeson and Caston, 2004). Leeson and Summers (2005) reported that yellow corn grains have about 20 ppm of xanthophylls and corn DDGS it is expected that may by a good source of xanthophylls pigment, because of their concentration during the production process.…”
Section: Content Of Pigmentsmentioning
confidence: 99%
“…A páprica apresenta entre 4 e 8 g/kg de xantofilas, sendo 50 a 70% capsantina, um pigmento vermelho-alaranjado (Galobart et al, 2004). Os pigmentos são absorvidos no íleo juntamente com os ácidos graxos, na forma de micelas, são esterificados e armazenados principalmente no tecido adiposo e na pele como hidroxicarotenoides (Pérez-Vendrell et al, 2001).…”
Section: Introductionunclassified